Analysis of Law Enforcement of Illegal Logging in Lokapaksa Village Protected Forest Area - Komang Cipta Rahayu Oktaviantari; A.A Istri Dewi Adhi Utami; Ni Nyoman Asri Sidaryanti; Clhodia Babalona Br Gurusinga; Ni Kadek Risti Ulan Deliani; I Gusti Putu Juliana Permana Putra; Siva Kusnia Nur Febrianti; Gede Diva Sastra Wiguna (Jurnal Ilmiah Ilmu Sosial, 2026)
Indonesia, as an archipelago rich in forest resources, faces serious threats in the form of illegal logging, including in the protected forest area of Lokapaksa Village, Buleleng Regency. This study aims to analyze the implementation of law enforcement against illegal logging perpetrators, by examining the legal framework, the effectiveness of legal implementation, the role of the community through the Village Forest Management Institution (LPHD), as well as obstacles and relevant supervision strategies. This research uses a descriptive qualitative method with an empirical legal approach, focusing on social facts that occur in the field (law in action). The research setting was Banjar Dinas Sorga Mekar, Lokapaksa Village. The research subjects included the Village Head, the Head of LPHD, and local community leaders. The object of the research is the practice of illegal logging and the law enforcement efforts made. Data collection techniques used in-depth interviews, direct observation, and analysis of documents relevant to the topic. Data were analyzed descriptively qualitatively to gain a thorough understanding. The results show that weak supervision, economic pressure, and lack of inter-agency coordination are the main factors that have not optimized law enforcement. This research recommends increasing the capacity of LPHD, applying strict sanctions that provide a deterrent effect, and strengthening the synergy between law enforcement, communities, and village governments on an ongoing basis.